The Urgency of Islamic Religious Education Learning Design Development in the Digital Era: Challenges and Implementable Solutions - Fito Amirul Pradonansyah; Firmansyah; Ani Aryati (PT. Pusmedia Group Indonesia, 2025)
Digital transformation has fundamentally reshaped educational paradigms, creating urgent demands for pedagogical adaptation in Islamic Religious Education (PAI). Despite PAI's critical role in character formation, a significant gap exists between traditional teacher-centered instruction and the needs of digital native students, threatening the relevance of Islamic education. This research aims to identify the urgency of developing innovative PAI learning designs in the digital era, analyze the main challenges faced, and formulate implementable solutions to increase student engagement and understanding. Key barriers include infrastructural inequalities, inconsistent teacher technological competencies, and concerns about maintaining Islamic values' authenticity in digital contexts. This study uses a descriptive method with a literature review approach. The results show that digital-based PAI learning design requires three main components: careful planning with analysis of digital native students' needs, implementation integrating interactive digital media and innovative methods such as gamification and blended learning, and comprehensive technology-based evaluation systems. Crucial supporting factors include technology readiness in schools, active parental involvement, and continuous teacher training in educational technology. The main challenges identified include limited technology access, variations in teachers' technological competence, sustainability of instilling Islamic values digitally, and risks of technological distractions. Recommended solutions include collaboration between schools, parents, and community, ongoing teacher training, structured learning approaches, and introduction of Islamic digital ethics. These results provide guidance for PAI educators in presenting relevant, interactive, and inspiring learning in the digital era while remaining consistent with Islamic education's core goals in shaping students' character and noble morals.